Legal Protection for Employees Who Continue to Work During Eid Al-Fitr (Sudi SPBU Pertamina Majapura Village, Bobotsari Subdistrict) - Arnando, Faisal (Proceedings Series on Social Sciences & Humanities, 2023)
Eid al-Fitr is a special day, because on this day almost all industrial sectors and offices are closed to all employees. The reason for this is so that workers can perform worship and gather with their loved ones. However, not all workers can experience Eid al-Fitr with their families because they have to keep working on that day. One of the work sectors that requires workers to continue working on Eid al-Fitr is the fuel oil and gas industry, this has been regulated in the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia Number: KEP.233 /MEN/2003 concerning Types and Nature of Work Performed Continuously. Although there are legal rules that are binding and compelling, on the other hand, it should also be noted that there are workers’ rights that must be fulfilled by the employer. The reality is that when Pertamina gas station workers in Majapura Village, Bobotsari Subdistrict work during Eid al-Fitr, they do not get the fulfilment of their rights that they should get. This sparked the author to compile this article with the aim of providing knowledge of legal protection that should be obtained by Pertamina gas station workers in Majapura Village, Bobotsari District with empirical juridical research methods and sociological approach methods.